2004
DOI: 10.1051/vetres:2003043
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Teladorsagia circumcincta and Trichostrongylus colubriformis worm populations by grazing sheep with differing resistance status

Abstract: -In an experiment lasting 4 years, changes in the Teladorsagia circumcincta andTrichostrongylus colubriformis populations were compared in lambs and adult sheep with differing resistance statuses. Two flocks of 30 rams (resistant R and susceptible S) grazed separate pastures and 8 rams were slaughtered in the middle and at the end of each grazing season. Five groups of tracer lambs were added each year to estimate the pasture infectivity and were killed for worm counts. The availability of animals with differi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
(25 reference statements)
0
14
0
2
Order By: Relevance
“…There is a significant association between increased IgA activity against larvae and reduced Hc female length (Strain & Stear, 2001;Saddiqi et al, 2011). Moreover, host breed (Aumont et al, 2003), host gender (Gruner et al, 2004), diet (Hoste et al, 2008) and concurrent parasitic infection (Reinecke et al, 1982;Terefe et al, 2005) can affect nematode length. Morphological features that detect the length of a specific character used in species identification may be affected as well.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant association between increased IgA activity against larvae and reduced Hc female length (Strain & Stear, 2001;Saddiqi et al, 2011). Moreover, host breed (Aumont et al, 2003), host gender (Gruner et al, 2004), diet (Hoste et al, 2008) and concurrent parasitic infection (Reinecke et al, 1982;Terefe et al, 2005) can affect nematode length. Morphological features that detect the length of a specific character used in species identification may be affected as well.…”
Section: Discussionmentioning
confidence: 99%
“…circumcincta developed in two stages: first, in association with the development of a specific local IgA response that resulted in the reduction of average egg production per worm; and second, in association with the production of globule leucocytes in the abomasal mucosa that resulted in the control of number of worms. In several studies, the number of globule leucocytes was negatively correlated with the number of worms, suggesting that this cell type has a specific role in the resistance of the host (Douch et al, 1986;Stear et al, 1995;Balic et al, 2000b;Gruner et al, 2004). Significant differences in the globule leucocyte counts were also reported in St. Croix (resistant) and Dorset (susceptible) sheep (Gamble and Zajac, 1992) and Crioula Lanada sheep (resistant) and in Corriedale (susceptible) lambs (Bricarello et al, 2004).…”
Section: Mast Cellsmentioning
confidence: 99%
“…It has been reported that mast cell counts in both the abomasal and the intestinal mucosa have an inverse relation to the length of female worms in both resistant and susceptible rams (Gruner et al, 2004) with Tel. circumcincta, and a positive correlation between mast cells and worm fecundity has also been reported.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Evaluation of estimated breeding values for FAMACHA scores indicate its heritability (Riley and Van Wyk, 2009) and has now been used as a phenotypic marker for selection in Brazil (Molento et al, 2009). However, FEC has been the most widely-used parameter in identifying sheep nematode resistance (Smith et al, 1984;Gill, 1991;Gruner et al, 2004;Davies et al, 2005). Heritability values vary from 0.30 -0.48 in T. circumcincta (Stear et al, 2009), T. colubriformis (Sreter et al, 1994;Douch et al, 1996) and H. contortus (Gruner et al, 2004) making it a viable indicator trait for selection.…”
Section: Breeding For Resistance To Gastrointestinal Nematodesmentioning
confidence: 99%
“…However, FEC has been the most widely-used parameter in identifying sheep nematode resistance (Smith et al, 1984;Gill, 1991;Gruner et al, 2004;Davies et al, 2005). Heritability values vary from 0.30 -0.48 in T. circumcincta (Stear et al, 2009), T. colubriformis (Sreter et al, 1994;Douch et al, 1996) and H. contortus (Gruner et al, 2004) making it a viable indicator trait for selection. The genetic component of FEC is further evidenced by its association with three different genotypes at the diallelic adenosine deaminase locus (Gulland et al, 1993) and major histocompatibility complex (MHC)-linked microsatellites in a wild population of Soay sheep (Beraldi et al, 2007).…”
Section: Breeding For Resistance To Gastrointestinal Nematodesmentioning
confidence: 99%